Self-Correction in Writing a Paragraph - Fergina Lengkoan; Sanerita Tresnawaty Olii (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
A paragraph is a subject consisting of a writer's developed related statements. In writing a paragraph, the students make sure their paragraph is in the correct format. This qualitative study describes students' writing development in a paragraph and the impact of self-correction. The study participants were 15 students in the second semester of a basic writing class at the English Education Department. The tests implemented were pre-test and post-test after five meetings of treatment. In the treatment, the students gave feedback about the paragraph, punctuation, capitalization, simple sentence, compound sentence, complex sentence, and compound-complex sentence. The results showed that self-correction benefited students' writing skills, and there was a development in their writing skills. This study suggested that self-correction was an effective method and was shown to be an appropriate method to improve the students’ writing skills.